2011
DOI: 10.1111/j.1523-5378.2011.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori and the Birth Cohort Effect: Evidence for Stabilized Colonization Rates in Childhood

Abstract: Background The prevalence of Helicobacter pylori has declined over recent decades in developed countries. The increasing prevalence with age is largely due to a birth-cohort effect. We previously observed a decline in H. pylori prevalence in 6- to 8-year old Dutch children from 19% in 1978 to 9% in 1993. Knowledge about birth-cohort-related H. pylori prevalence is relevant as a predictor for the future incidence of H. pylori-associated conditions. Aim The aim of this study was to investigate whether the birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 39 publications
2
38
2
3
Order By: Relevance
“…In previous studies, insufficient numbers of subjects with colorectal neoplasia were enrolled compared to our study. We included patients with a history of colorectal neoplasia found on previous colonoscopies, since H. pylori infection is acquired during childhood and adolescence [7] with almost no new infections in adulthood [20], thus increasing the number of diagnosed colorectal neoplasia after age adjustment. Deciding on the patients' outcome status only from the last current colonoscopy without referring to previous colonoscopic results, which may contain information about polyps or cancer lesions that have been removed in the past, could cause misclassification into the negative group (no findings) of patients that actually have had neoplastic lesions in their past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, insufficient numbers of subjects with colorectal neoplasia were enrolled compared to our study. We included patients with a history of colorectal neoplasia found on previous colonoscopies, since H. pylori infection is acquired during childhood and adolescence [7] with almost no new infections in adulthood [20], thus increasing the number of diagnosed colorectal neoplasia after age adjustment. Deciding on the patients' outcome status only from the last current colonoscopy without referring to previous colonoscopic results, which may contain information about polyps or cancer lesions that have been removed in the past, could cause misclassification into the negative group (no findings) of patients that actually have had neoplastic lesions in their past.…”
Section: Discussionmentioning
confidence: 99%
“…If the second examination was also incomplete, the results were excluded from the analysis. Since H. pylori infection is acquired mostly during childhood and adolescence [7] with almost no new infections in adulthood [20], we searched the participants' medical files for previous colonoscopies and included positive findings of neoplastic lesions instead of the present negative findings, since colonoscopy after a previous polypectomy can be negative. Thus, using only present colonoscopy findings without taking into account previous findings, can lead to underestimation of the association.…”
Section: Colonoscopymentioning
confidence: 99%
“…Ennek ellentmond, hogy egy holland tanulmányban a H. pylori kolonizációja gyermekekben 1978 és 1992 között csökkent, de 1993-2005-ben stabil, 9% (95% KT: 6,6-11,4%) értéken maradt. Ezt a szerzők a szociális ténye-zők és higiénés feltételek változatlan színvonalával magyarázták [18].…”
Section: Megbeszélésunclassified
“…Some recent data suggest that this phenomenon may have slowed down or come to a halt, which is likely related to stabilization of environmental exposure. A further Dutch study using the same methods found that the prevalence of H. pylori had stabilized at 9% in children aged 7-9 years between 1993 and 2006 [5]. The cause of this apparent stabilization remains unclear.…”
Section: Lifestyle and Helicobacter Pylori Colonizationmentioning
confidence: 99%